2012
DOI: 10.1126/science.338.6114.1537-b
|View full text |Cite
|
Sign up to set email alerts
|

Mobilizing Religion and Conservation in Asia

Abstract: This paper is NOT THE PUBLISHED VERSION; but the author's final, peer-reviewed manuscript. The published version may be accessed by following the link in th citation below.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Given the serious risks that PARs pose to the environment and to biodiversity, conservation organizations (eg the Society for Conservation Biology, SCB) have called for immediate actions to curb the likely adverse effects of PARs. Such actions include educating particular religious groups about the risks involved with PARs, enforcing regulations and laws, providing alternatives to PARs, and monitoring of biodiversity at PAR sites (Agoramoorthy and Hsu 2005;Awoyemi et al 2012Awoyemi et al , 2016Magellan 2019). Although the potential ecological and environmental issues caused by PARs are disconcerting to academics and the general public alike, the potential risk of PAR-related species invasions has never been fully evaluated.…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…Given the serious risks that PARs pose to the environment and to biodiversity, conservation organizations (eg the Society for Conservation Biology, SCB) have called for immediate actions to curb the likely adverse effects of PARs. Such actions include educating particular religious groups about the risks involved with PARs, enforcing regulations and laws, providing alternatives to PARs, and monitoring of biodiversity at PAR sites (Agoramoorthy and Hsu 2005;Awoyemi et al 2012Awoyemi et al , 2016Magellan 2019). Although the potential ecological and environmental issues caused by PARs are disconcerting to academics and the general public alike, the potential risk of PAR-related species invasions has never been fully evaluated.…”
mentioning
confidence: 99%
“…The number of animals involved in PAR events is staggering (Awoyemi et al . 2012). For example, the Buddhist China Preserve Life Association reported that more than 20 million animals—the vast majority of which were small aquatic species—were released in at least 300 ceremonies conducted in 2008 alone (Awoyemi et al .…”
mentioning
confidence: 99%
See 3 more Smart Citations